Dynamic miRNA profile of host T cells during early hepatic stages of Schistosoma japonicum infection - Giri, Bikash R.; Li, Shun; Fang, Chuantao; Qiu, Lin; Yan, Shi; Pakharukova, Maria Y.; Cheng, Guofeng (Frontiers in Immunology, 2022)
Schistosomes undergo complicated migration in final hosts during infection, associated with differential immune responses. It has been shown that CD4+ T cells play critical roles in response to Schistosoma infections and accumulated documents have indicated that miRNAs tightly regulate T cell activity. However, miRNA profiles in host T cells associated with Schistosoma infection remain poorly characterized. Therefore, we undertook the study and systematically characterized T cell miRNA profiles from the livers and blood of S. japonicum infected C57BL/6J mice at 14- and 21-days post-infection. We observed 508 and 504 miRNAs, in which 264 miRNAs were co-detected in T cells isolated from blood and livers, respectively. The comparative analysis of T cell miRNAs from uninfected and infected C57BL/6J mice blood showed that miR-486b-5p/3p expression was significantly downregulated and linked to various T cell immune responses and miR-375-5p was highly upregulated, associated with Wnt signaling and pluripotency, Delta notch signaling pathways, etc. Whereas hepatic T cells showed miR-466b-3p, miR-486b-3p, miR-1969, and miR-375 were differentially expressed compared to the uninfected control. The different expressions of some miRNAs were further corroborated in isolated T cells from mice and in vitro cultured EL-4 cells treated with S. japonicum worm antigens by RT-qPCR and similar results were found. In addition, bioinformatics analysis combined with RT-qPCR validation of selected targets associated with the immune system and parasite-caused infectious disease showed a significant increase in the expression of Ctla4, Atg5, Hgf, Vcl and Arpc4 and a decreased expression of Fermt3, Pik3r1, Myd88, Nfkbie, Ppp1r12a, Ppp3r1, Nfyb, Atg12, Ube2n, Tyrobp, Cxcr4 and Tollip. Overall, these results unveil the comprehensive repertoire of T cell miRNAs during S. japonicum infection, suggesting that the circulatory (blood) and liver systems have distinct miRNAs landscapes that may be important for regulating T cell immune response. Altogether, our findings indicated a dynamic expression pattern of T cell miRNAs during the hepatic stages of S. japonicum infection.